2022
DOI: 10.3390/md20050296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antiviral Effect against SARS-CoV-2 Propagation by Crude Polysaccharides from Seaweed and Abalone Viscera In Vitro

Abstract: Crude polysaccharides, extracted from two seaweed species (Hizikia fusiforme and Sargassum horneri) and Haliotis discus hannai (abalone) viscera, were evaluated for their inhibitory effect against SARS-CoV-2 propagation. Plaque titration revealed that these crude polysaccharides efficiently inhibited SARS-CoV-2 propagation with IC50 values ranging from 0.35 to 4.37 μg/mL. The crude polysaccharide of H. fusiforme showed the strongest antiviral effect, with IC50 of 0.35 μg/mL, followed by S. horneri and abalone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The results of plaque titration showed that these crude polysaccharides effectively inhibited the spread of SARS-COV-2. 136 Among them, S. f usiforme crude polysaccharides has the strongest antivirus effect. Moreover, treatment of crude polysaccharides can strongly inhibit the expression levels of SARS-COV-2 spike, nucleocapsid protein, and RNA polymerase in the Vero cells model.…”
Section: Antivirus and Antibacterial Activitiesmentioning
confidence: 88%
See 3 more Smart Citations
“…The results of plaque titration showed that these crude polysaccharides effectively inhibited the spread of SARS-COV-2. 136 Among them, S. f usiforme crude polysaccharides has the strongest antivirus effect. Moreover, treatment of crude polysaccharides can strongly inhibit the expression levels of SARS-COV-2 spike, nucleocapsid protein, and RNA polymerase in the Vero cells model.…”
Section: Antivirus and Antibacterial Activitiesmentioning
confidence: 88%
“…Kang et al evaluated the inhibitory effect of the crude polysaccharides extracted from two kinds of algae ( S. fusiforme and S. horneri ) and Haliotis discus hannai viscera on the spread of SARS-COV-2. The results of plaque titration showed that these crude polysaccharides effectively inhibited the spread of SARS-COV-2 . Among them, S. fusiforme crude polysaccharides has the strongest antivirus effect.…”
Section: Bioactivities Of S Fusiformementioning
confidence: 98%
See 2 more Smart Citations
“…Polysaccharides from herbal materials are well-known for their immunomodulation effects. Polysaccharides from seaweed were found to inhibit SARS-CoV-2 propagation by blocking viral entry [ 33 ]. Together, these data suggest that different types of carbohydrates could have an important role in the prevention of SARS-CoV-2, beyond the action of just the organic principal components.…”
Section: Discussionmentioning
confidence: 99%